The Wealth of Medicinal Plant Species in the Protective Forest Area of Mount Ungaran, Ngesrepbalong Village, Kendal Regency - Elsa Septiani Rintho Miharjo; Ary Susatyo Nugroho; Fibria Kaswinarni (Program Studi Pendidikan Biologi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kuningan, 2025)
During modernization and the trends of modern medicine, the use of traditional medicines remains relevant, especially in rural and remote areas. This research aims to identify the types, relative abundance, benefits, and utilization of medicinal plants in the Ngesrepbalong Village, Kendal Regency. The research methods applied include field surveys and interviews to identify, record, and understand the benefits and utilization of various types of wild medicinal plants. The results of the research show that the Gunung Ungaran Protective Forest area harbors significant diversity in terms of types of medicinal wild plants. In the Gunung Ungaran Protective Forest area, Ngesrepbalong Village, Kendal Regency, there are 40 types of medicinal wild plants. The most abundant species include krinyu, pecut kuda, cakar ayam, and bandotan, while the least abundant species are tejo and kina. These plants are utilized as external medicines, such as for topical application or as ingredients in bathwater, as well as internal medicines, which can be consumed orally.This study is expected to serve as a foundation for environmental conservation efforts and the wise utilization of biological resources to support public health.